The Effect of Family Environment and School Environment Towards Savings Behavior Through Self Control in High School Students in Purwodadi City, Grobogan Regency - Ningsih, Rahayu Setya; Widiyanto, Widiyanto; Sudarma, Ketut (Journal of Economic Education, 2018)
Savings behavior is important to start early so that it can educate children to be able to control themselves from consumptive manner, learn to be able to spend money wisely. Savings activities have also trained children to grow into a community that is skilled in financial management. The objectives of this study are to find out the effect of family and school environment on self-control and find out the effect of the family and school environment and self-control on students' saving behavior. This type of research was a quantitative with a correlational approach. The research sample was 324 students with proportional stratified random sampling technique. The data analysis techniques used path analysis. The family and school environment have a positive and significant effect on students' self-control. Family environment, school environment, and self-control have a positive and significant effect on students' saving behavior.